2017
DOI: 10.1097/prs.0000000000003120
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Subfascial Calf Augmentation

Abstract: Therapeutic, V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Many surgeons and physicians have thus been looking for ways of correcting or altering the forms and volumes of calves and upper arms. [1][2][3] In fact, the popularity of arm lifting (brachioplasty) has grown rapidly in previous years, with a 2017 top 5 ranking for the fastest growing surgical procedures with more than 18,000 performed procedures in a single year. 4 Similarly, for calves, the most popular procedure is surgery, specifically the insertion of calf implants or autologous tissue transfer.…”
Section: Introduction Imentioning
confidence: 99%
“…Many surgeons and physicians have thus been looking for ways of correcting or altering the forms and volumes of calves and upper arms. [1][2][3] In fact, the popularity of arm lifting (brachioplasty) has grown rapidly in previous years, with a 2017 top 5 ranking for the fastest growing surgical procedures with more than 18,000 performed procedures in a single year. 4 Similarly, for calves, the most popular procedure is surgery, specifically the insertion of calf implants or autologous tissue transfer.…”
Section: Introduction Imentioning
confidence: 99%
“…We are convinced of the essential benefits of using 3D elastomer implants rather than classic gel-filled standard implants. The lack of implant models and choice of available sizes was recently strongly emphasized by Andjelkov et al 3 Moreover, we believe that we have demonstrated the value of computer-aided design and rubber elastomer for the correction of congenital thoracic malformations such as pectus excavatum 4 and Poland syndrome. 5 Overall, these implants are not likely to rupture in the long term and are in place for life.…”
mentioning
confidence: 61%
“…In recent years, both women and men have shown an increasing interest in the appearance of their thighs and calves, which has run along with the increasing demand of aesthetic procedures of this area. 2–22 In the US in 2018, there were 10,100 thigh lifts performed, 9614 in women (95.1%) and 486 in men (4.8%), and also 655 calf augmentations, 377 in men (58%) and 278 in women (42%). 23 Surprisingly, our population showed a different distribution, as men required less calf augmentations compared with women, and women actually sought the appearance of stronger legs and more voluminous thighs compared with men.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Although they may improve the overall appearance of the leg, their use has several potential complications, including hyperpigmentation, seromas, extrusion, infection, capsular contracture, secondary surgery, and compartment syndrome. 1,[8][9][10] Comparatively, fat grafting is likely to volumize the leg with a reduced likelihood of complications due to the autologous nature of the tissue transfer. We did an anatomical review and cadaveric dissections of the quadriceps and the gastrocnemius muscles before and after our fat grafting technique to provide safety recommendations.…”
Section: Introductionmentioning
confidence: 99%